New art of living - "Peale, Norman Vincent" (London, 2010)
About The Author: Clergyman and author Norman Vincent Peale was born in Bowersville, Ohio, on May 31, 1898. He was ordained into the Methodist Episcopal Church in 1922 and served as a pastor in a variety of churches in the eastern United States for the next decade. In 1932, he joined the Dutch Reformed Church and became the pastor of the Marble Collegiate Church, a post he would hold for more than fifty years. Peale's book, The Power of Positive Thinking, has sold more than fifteen million copies and been translated into forty languages. It helped create a viable market for self-help books. In addition to writing, he gave sermons on both television and radio and published Guideposts, a very successful weekly newsletter. He died on Christmas Eve, 1993.
Keywords: Christian life and practice